DASAR-DASAR PENDIDIKAN ISLAM DALAM TINJAUANAL-QUR’AN DAN AL- HADIST - Abd Rahman Fasih (IAIN PAREPARE, 2016)
Islamic education is the epistemological bases itself on a certain paradigm in this case is Islam as the main reference. Traditionally the word Islam implies two things: al quran and hadith. The second source is the primary source of epistemic in the construction of Islamic education. This paper has mapped the alQuran and Hadith as an authentic source for the sustainability of Islamic education. This article uses text analysis considering the verses and hadiths are used as justification in establishing its existence. The results showed that there was significant difference between the Islamic and western education system (secular). If the Western education system bases itself only in the framework of rationality, the Islamic educational system basing himself on al quran and hadith.